2014
DOI: 10.5130/ccs.v6i1.3714
|View full text |Cite
|
Sign up to set email alerts
|

Whale Watching as Ecotourism: How Sustainable is it?

Abstract: Whale Watching as an alternative to the practice of commercial and 'scientific' whaling has evolved as an ecotourism activity. This paper explores whale watching in an effort to determine its economic and social viability as a sustainable, marine tourism activity -and whether the whale and the tourist can coexist in the future. We define whale watching as an ecotourism product, as it holds the potential for sustainable practice, one that is both ecologically sound and profitable. Responsible whale watching is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Potential negative impacts of whale watching activities have been reported to be derived from disturbance reasons, with consequent stress index increases and behavioral changes (Magalhaes et al, 1999;Erbe, 2002;Lusseau, 2006;Richter et al, 2006;Visser et al, 2011;Parsons, 2012;New et al, 2015). At the same time, it has been demonstrated that whale-watching can be an effective tool to raise awareness about species conservation issues and to educate tourists on cetaceans' ecology and threats, especially when the tourist experience is enriched by good environmental education (Lien, 2001;Lück, 2003;Stamation et al, 2007;Wearing et al, 2014;García-Cegarra and Pacheco, 2017;La Manna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Potential negative impacts of whale watching activities have been reported to be derived from disturbance reasons, with consequent stress index increases and behavioral changes (Magalhaes et al, 1999;Erbe, 2002;Lusseau, 2006;Richter et al, 2006;Visser et al, 2011;Parsons, 2012;New et al, 2015). At the same time, it has been demonstrated that whale-watching can be an effective tool to raise awareness about species conservation issues and to educate tourists on cetaceans' ecology and threats, especially when the tourist experience is enriched by good environmental education (Lien, 2001;Lück, 2003;Stamation et al, 2007;Wearing et al, 2014;García-Cegarra and Pacheco, 2017;La Manna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A starting point for considering Important Marine Mammals Areas (IMMA) criteria to protect single species or a combination of species are [267] In the pelagic realm frequented by cetaceans, it is likely that at least in some instances site-based conservation approaches are not going to be sufficient, or even suitable [267]. However, IMMAs, being a new development, provide an opportunity to explore how static notions of MPAs can merge with more flexible modern management interventions, supporting 'dynamic ocean management' [268,269]. Various data streams, such as from tracking and remote sensing technologies, could conceivably be fused together to support near realtime decision-making on where a given IMMA is and in which direction it is headed [267].…”
Section: Marine Protected Areasmentioning
confidence: 99%
“…Whale watching has become a significant sector of the nature-based tourism industry (Higginbottom, 2004). Commercial whale watching started in the 1980s and is categorized as an ecotourism activity because it can be ecologically sustainable while simultaneously fostering cultural and environmental appreciation for the marine environment (O'Connor et al, 2009;Wearing et al, 2014). Whale watching is considered a viable alternative to whaling (Einarsson, 2009;Cunningham et al, 2012), as it also supports coastal communities and offers them a sense of identity and pride (Hoyt, 2001;Rossing, 2006;Hoyt and Iñíguez, 2008;Peake et al, 2009;Cisneros-Montemayor et al, 2010;Schwoerer et al, 2016;Guidino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%